1998
DOI: 10.1007/s11661-998-1015-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tungsten particle shape on dynamic deformation and fracture behavior of tungsten heavy alloys

Abstract: The effect of the tungsten particle shape on the dynamic deformation and fracture behavior of tungsten heavy alloys was investigated. Dynamic torsional tests were conducted using a torsional Kolsky bar for five alloys, one of which was fabricated by the double-cycled sintering process, and then the test data were compared via microstructures, mechanical properties, adiabatic shear banding, and fracture mode. The dynamic torsional test results indicated that in the double-sintered tungsten alloy whose tungsten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…However, penetrators that have too high strength are easily embrittled, and, thus, their penetration performance deteriorates because of fragmentation during penetration. It is desirable for a penetrator to have deformation behavior that can be induced self-sharpening and possess sufficient fracture toughness to minimize fragmentation during high-speed impact [142]. A shear band forms at the point on the rods mantle where the mushroomed region transitions into the straight rod, which agreed qualitatively with Dick et al [149].…”
Section: Penetrator Performancesupporting
confidence: 73%
See 1 more Smart Citation
“…However, penetrators that have too high strength are easily embrittled, and, thus, their penetration performance deteriorates because of fragmentation during penetration. It is desirable for a penetrator to have deformation behavior that can be induced self-sharpening and possess sufficient fracture toughness to minimize fragmentation during high-speed impact [142]. A shear band forms at the point on the rods mantle where the mushroomed region transitions into the straight rod, which agreed qualitatively with Dick et al [149].…”
Section: Penetrator Performancesupporting
confidence: 73%
“…The ASB has general trends to propagate along the Ni-Fe matrix because more energy is needed to shear the W grains. The influence of the microstructure such as heterogeneity, the content of matrix, and the particle shape on shear band formation is reported [29,142] compression (strain rate ∼ 10 3 s −1 ) [143]. The true stresstrue strain curves of the UFG-W exhibit significant flow softening, and the peak stress is ∼3 GPa.…”
Section: Penetrator Performancementioning
confidence: 99%
“…Recently, several studies have been performed to enhance the mechanical properties of WHAs in order to improve the penetration for kinetic energy penetrators [8][9][10][11]. Many publications on the enhancement of the mechanical properties by controlling the microstructural factors in WHAs have been reported [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the compressive flow stress of this tungsten heavy alloy increases with the increasing of strain rates from 10 −4 s −1 up to about 7.0 × 10 3 s −1 . Kim et al [10][11] studied the effect of the size and shape of tungsten particles on dynamic torsional properties in tungsten heavy alloys and reported that the size of tungsten particles and their hardness were increased as sintering temperature and time were increased and there would be an appropriate tungsten particle size because the cleavage fracture mode would be beneficial for the "self-sharpening" of the tungsten heavy alloys.…”
Section: Introductionmentioning
confidence: 99%